Pakiety gwarancji pracowniczych w procesach zmian stabilizatory czy hamulce procesu? - Czapiewski, Mirosław (Package of employees benefit in changing process - stabilizer or brake?, 2006)
Restructuring and privatization process held in polish organizations have come to another stage of realization. This phase differs from optimism which is connected with restructuring and privatization process, taking place in the nineties. Those actions were combined with a lack of social confidence. Even the best and properly prepared strategies must face with social resistance and could not be brought into effect. At the turn of the nineties and twenties, the social expectations concerning employment are increasing. Employees concerns and claims are attributed to social agreements named package of employees benefit. Author relying on his own experience and study of the case is trying to answer this statement as far those agreements are stabilizer of mentioned process or do they slow down it and arouse employees hopes which rises the cost of the changes.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 547-555